2023
DOI: 10.1002/ange.202300379
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis Detection: From Approaches to Applications

Abstract: Understanding the intricate molecular machinery that governs ferroptosis and leveraging this accumulating knowledge could facilitate disease prevention, diagnosis, treatment, and prognosis. Emerging approaches for the in situ detection of the major regulators and biological events across cellular, tissue, and in living subjects provide a multiscale perspective for studying ferroptosis. Furthermore, advanced applications that integrate ferroptosis detection and the latest technologies hold tremendous promise in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 163 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Apoptosis and ferroptosis are two common mechanisms of cell death, and differentiation between them is essential for understanding cell biology and developing corresponding therapeutic strategies. Apoptosis is typically accompanied by DNA degradation, whereas ferroptosis is caused by the disruption of the cellular redox balance (Figure a). Apoptosis is characterized by nuclear changes, such as chromatin condensation, nuclear shrinkage, DNA fragmentation, and the formation of apoptotic bodies; in contrast, ferroptosis does not involve these nuclear changes. Therefore, we investigated whether SPP could track DNA damage in mitochondria and nuclei during apoptosis and ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis and ferroptosis are two common mechanisms of cell death, and differentiation between them is essential for understanding cell biology and developing corresponding therapeutic strategies. Apoptosis is typically accompanied by DNA degradation, whereas ferroptosis is caused by the disruption of the cellular redox balance (Figure a). Apoptosis is characterized by nuclear changes, such as chromatin condensation, nuclear shrinkage, DNA fragmentation, and the formation of apoptotic bodies; in contrast, ferroptosis does not involve these nuclear changes. Therefore, we investigated whether SPP could track DNA damage in mitochondria and nuclei during apoptosis and ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
“…The targeting peptides assist in enhancing the specific labeling and uptake of probes, such as proteins and cell membranes; therefore, the CCI NPs probes provides two important advantages for feMPI: (i) enhanced retention time in target tissues; (ii) the signal intensity has a linear correlation with the percent infarct area stained by TTC staining, allowing for a quantitative assessment of the extent of heart damage. Previous studies have reported methods for visualizing ferroptotic molecules using fluorescence, PET, or MRI [33] [34] . To the best of the authors' knowledge, the novel research here has elaborated upon the specificity of green, safe materials and simple synthesis methods for preparing in vivo probes to visualize MI/R-induced cardiac injury using feMPI.…”
Section: Discussionmentioning
confidence: 99%